Microstructure and mechanical properties of a nanostructured Mg-8.2Gd-3.8Y-1.0Zn-0.4Zr supersaturated solid solution prepared by high pressure torsion. (5th December 2017) - Sun, W.T.; Qiao, X.G.; Zheng, M.Y.; Xu, C.; Gao, N.; Starink, M.J.
Abstract: In this study, a solution-treated Mg-8.2Gd-3.8Y-1.0Zn-0.4Zr (wt%) alloy was processed by high pressure torsion (HPT) at room temperature, with the aim of producing a material with exceptional mechanical properties. Transmission electron microscopy and X-ray diffraction line broadening analysis reveal that a nanostructured supersaturated solid solution with a mean grain size of ~ 48 nm and high dislocation density of ~ 4.7 × 10 14  m − 2 is achieved by HPT deformation. After HPT processing, the present solution-treated samples show finer grains and higher dislocation densities as compared to as-cast samples of this alloy, other solution-treated Mg-RE alloys and conventional Mg alloys deformed using similar HPT processing conditions. This could be attributed to retardation of the dislocation annihilation through enhanced solute-dislocation and/or dislocation-dislocation interactions. The higher dislocation density and nanosized grains within supersaturated solid solution cause the microhardness to increase to ~ 126 HV, which is higher than that of the as-cast Mg-8.2Gd-3.8Y-1.0Zn-0.4Zr (wt%) alloy processed by HPT, and is also higher than that of any conventional Mg-rich alloy deformed using HPT. Graphical abstract: Highlights: A nanostructured Mg-Gd-Y-Zn-Zr supersaturated solid solution is achieved by high pressure torsion at room temperature. High dislocation density and nanosized grains of supersaturated solid solution cause the microhardness increase to ~ 126 HV. High solute content increases the dislocation density by enhancing solute-dislocation/dislocation-dislocation interactions.